DNA barcoding reveals taxonomic uncertainty in Salminus (Characiformes). Issue 4 (4th July 2017) - Machado, Carolina De Barros; Ishizuka, Tamylin Kaori; Freitas, PatrÍcia Domingues De; Valiati, Victor Hugo; Galetti, Pedro Manoel
Abstract : Salminus is a genus composed of four species of migratory fishes and top predators. Although this group has great economic and ecological importance, the species level diversity of Salminus is not yet completely clarified. Our goal was to detect if this taxonomic problem is the consequence of lineage divergence within species, and, if so, whether these divergences are sufficient to flag potentially undescribed taxa. We employed the standard DNA barcoding analyses and a generalized mixed Yule-coalescent model (GMYC) using one mitochondrial (COI) marker and Bayesian Inference (BI) reconstruction for one nuclear (RAG2) marker for all currently recognized species of Salminus, sampled across different hydrographic basins. Eight MOTUs (Molecular Operational Taxonomic Units) were determined by distance and model-based analyses, and recovered with BI analyses for COI. Only Salminus affinis and Salminus franciscanus formed monophyletic haplogroups. Salminus brasiliensis and Salminus hilarii had two and four distinct mitochondrial lineages, respectively, and higher intraspecific K2P distances than the adopted optimum threshold. The RAG2 gene tree supported two lineages of S. hilarii ( S. hilarii Amazon and S . hilarii Araguaia), while the other mitochondrial lineages of S. hilarii and S. brasiliensis were not supported. All lineages of both species, corresponded to morphological variation described in previous studies. We suggest, based on the DNA barcoding analysis, a new taxonomic scenario and conservation polices for Salminus in the Brazilian territory.